Modelling the Effectiveness of Scrum Daily Using SEM: A Mathematical Model for Agile Teams - Rzepecka-Smolińska, Aleksandra (Efektywność Scrum Daily – wybrane aspekty, 2025)
In the world of modern business, where change is the only constant, traditional methods of managing IT projects are gradually fading into oblivion. More organizations are adopting agile methodologies to flexibly manage projects, continuously deliver value to customers, maximize team efficiency and quickly respond to changing business requirements. One of the most commonly used methods is Scrum, with the key event being the Daily Scrum – a short, daily team meeting aimed at synchronizing progress and addressing any obstacles in the project. The Scrum Guide, the official handbook for the method, provides clear guidelines on how to organize this event. However, despite following the same principles, many teams are not satisfied with the quality of their Daily Scrum. This study aims to address this issue by building a theoretical mathematical model that considers selected aspects (Communication, Sprint Goal, Timing, Team Autonomy, and Self-Management) and conducting a Structural Equation Modelling (SEM) analysis. The findings will help identify factors worth considering to make the Daily Scrum as effective as possible.
Quote as: Rzepecka-Smolińska, A. (2025). Modelling the Effectiveness of Scrum Daily using SEM: A Mathematical Model for Agile Teams. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 168-181). Publishing House of Wroclaw University of Economics and Business.
Keywords: scrum team; Scrum Daily; Scrum Daily effectiveness; structural equation modelling; zespół scrumowy; efektywność Scrum Daily; modelowanie równań strukturalnych